Az Európai Külügyi Szolgálat szerepe – út a szorosabb európai integráció felé? - Szabó, Fruzsina Mariann (Debreceni Jogi Műhely, 2014)
This essay examines the impact of the European External Action Service (EEAS) on the development of the European integration. First, the historical and institutional precedents, and the development of external institutional system of the EC (EU) are presented. Then it is mentioned in greater details which factors led to the establishment of the institution of the High Representative (HR) and its assisting European External Action Service. The EEAS’s role is analyzed and assessed primarily from the standpoint that – given its operation and power – how the creation of this institution can strengthen the achievement of a closer European integration. This issue is analyzed especially in relation with cooperation, and division of tasks and power with the other EU bodies and institutions that play decisive role in the implementation of the EU’s external actions.